2023
DOI: 10.1111/bjh.18807
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes in patients with chronic lymphocytic leukaemia infected during the omicron BA.5 subvariant surge

Abstract: Summary Patients with chronic lymphocytic leukaemia (CLL) infected with SARS‐CoV‐2 are at increased risk of severe COVID‐19 and death. The outcomes of CLL patients with COVID‐19 during the omicron subvariants and in particular with BA.5 are not fully elucidated. Here, we report the outcomes of 128 CLL patients diagnosed with COVID‐19 from December 2021 through November 2022. The hospitalization and 30‐day mortality rates were 26.6% (n = 34) and 4.7% (n = 6), respectively. Both hospitalizations and mortality we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Early studies of COVID-19 and CLL have indicated high mortality rates at approximately 30% among hospitalized patients [1,3]. The majority of COVID-19 positive CLL patients required hospitalization, especially in the beginning of the pandemic [3][4][5]. The rates for intensive care unit (ICU) admission and intensive treatments with oxygen supplements and mechanical ventilation were also excessive compared to patients without a hematological disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of COVID-19 and CLL have indicated high mortality rates at approximately 30% among hospitalized patients [1,3]. The majority of COVID-19 positive CLL patients required hospitalization, especially in the beginning of the pandemic [3][4][5]. The rates for intensive care unit (ICU) admission and intensive treatments with oxygen supplements and mechanical ventilation were also excessive compared to patients without a hematological disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of COVID-19 and CLL have indicated high mortality rates at approximately 30% among hospitalized patients [1,3]. The majority of COVID-19 positive CLL patients required hospitalization, especially in the beginning of the pandemic [3][4][5]. The rates for intensive care unit (ICU) admission and intensive treatments with oxygen supplements and mechanical ventilation were also excessive compared to patients without a hematological disease [6].…”
mentioning
confidence: 99%